2017
DOI: 10.1111/zsc.12265
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic history of subterranean isopods from groundwater calcrete islands in Western Australia

Abstract: Groundwater calcretes in arid central Western Australia contain a diverse invertebrate groundwater fauna (stygofauna). Surveys have uncovered a diverse oniscidean isopod subterranean fauna above the water table (troglofauna), including species of a recently described genus Paraplatyarthrus. The aim of this study was to investigate the biogeographic history of Paraplatyarthrus and the timing of transitions from surface to subterranean habitats. Phylogenetic relationships among the isopod troglofauna from 11 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The selection analyses, and previous biogeographic analyses of the subterranean isopods (Javidkar et al, 2018 ), indirectly suggest that the calcrete aquifers have been fed with lignocellulose hydrocarbons for millions of years. This lignocellulose is likely to come from root systems that penetrate into the calcrete and down to the water table, where they also provide a direct (via root grazing) or indirect (via exudates) source of carbon for other crustaceans, such as Amphipoda and Copepoda, in the groundwater ecosystem; It has been suggested that exudates may be derived from termites in the terrestrial environment (Saccò et al, 2022 ), but it is also likely that subterranean isopods, by directly feeding on root material, also contribute to energy flows into the groundwater.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The selection analyses, and previous biogeographic analyses of the subterranean isopods (Javidkar et al, 2018 ), indirectly suggest that the calcrete aquifers have been fed with lignocellulose hydrocarbons for millions of years. This lignocellulose is likely to come from root systems that penetrate into the calcrete and down to the water table, where they also provide a direct (via root grazing) or indirect (via exudates) source of carbon for other crustaceans, such as Amphipoda and Copepoda, in the groundwater ecosystem; It has been suggested that exudates may be derived from termites in the terrestrial environment (Saccò et al, 2022 ), but it is also likely that subterranean isopods, by directly feeding on root material, also contribute to energy flows into the groundwater.…”
Section: Discussionmentioning
confidence: 71%
“…This shift in selective pressure could be linked to the evolutionary transition from surface to subterranean environments. It is estimated that this transition by Paraplatyarthrus species in WA took place between the mid‐Miocene and the Pleistocene, coinciding with the onset of aridification in Australia (Javidkar et al, 2018 ). Furthermore, branch‐site models of evolution (Model A, aBSREL, and BUSTED) provided evidence of positive selection for the subterranean species that may indicate novel adaptations to the subterranean environment at the associated amino acid sites.…”
Section: Discussionmentioning
confidence: 99%
“…While bores can act as large pitfall traps, depending on the location and size of the slots in the pipe, such results are not consistent between bores and frequently unknown. While there are methods to assess troglofaunal communities (e.g., litter traps, Javidkar et al, 2018), the application of eDNA‐based methods in this area is untested. Scrapes of soil from inside drilled holes may provide an adequate eDNA substrate; however, this is difficult on Barrow Island because the PVC casing of the bores prevents the collection of scrapes.…”
Section: Discussionmentioning
confidence: 99%
“…The scenario involves populations of hygrophilic epigean lineages colonising underground habitats where moisture and food conditions remained favourable, followed by extinction of their surface counterparts as surface conditions became inhospitable, thus facilitating allopatric speciation. Phylogenetic analyses conducted on troglobitic pseudoscorpions ( Harrison et al 2014 ), schizomids ( Abrams et al 2019 ; Harms et al 2018 ), isopods ( Javidkar et al 2018 ) and springtails ( Guzik et al 2020 ) suggested multiple colonisations by putative epigean ancestors and species radiations coinciding with aridification between 15 and 1.75 Ma. Despite the lack of molecular data to estimate the time of divergence amongst the Anillini taxa described so far, the ‘climatic relict’ hypothesis may help to explain their ecological and evolutionary shift to subterranean habitats in semi-arid environments.…”
Section: Discussionmentioning
confidence: 99%